2020
DOI: 10.1111/cote.12509
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Optical Society of America Uniform Color Scales system: past, present and future challenges

Abstract: As a tribute to Claudio Oleari (1944‐2018), in this article we remember some of his ideas about the role of physics and engineering in modern colour science. In particular, we consider his emphasis on the strong content of the work carried out during 1947‐1974 by the Committee on Uniform Scales of the Optical Society of America. Oleari considered the Optical Society of America Uniform Color Scales system a very useful basis for new developments in colour science, including approximately uniform colour spaces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, was demonstrated that the statistical differences reachable are marginal [14] and then the original formulation remains the more easily and reliably usable. Moreover, we compared the CIEDE2000 formula with the Euclidean color-difference formula for small-medium color differences in log-compressed OSA-UCS (Optical Society of America's committee on Uniform Color Scales) space [15,16]. Our attempt is inspired by the study [17], where the UCS diagram based on CIELUV color space is used to evaluate two color difference formulae ∆E00 and ∆EE for measuring the visual data.…”
Section: Experimental Setup and Tests Descriptionmentioning
confidence: 99%
“…However, was demonstrated that the statistical differences reachable are marginal [14] and then the original formulation remains the more easily and reliably usable. Moreover, we compared the CIEDE2000 formula with the Euclidean color-difference formula for small-medium color differences in log-compressed OSA-UCS (Optical Society of America's committee on Uniform Color Scales) space [15,16]. Our attempt is inspired by the study [17], where the UCS diagram based on CIELUV color space is used to evaluate two color difference formulae ∆E00 and ∆EE for measuring the visual data.…”
Section: Experimental Setup and Tests Descriptionmentioning
confidence: 99%
“…In SHAFT the optimization process is guided in the original formulation by an iterative CIEDE2000 variation comparison. In this work is presented a variant of the framework replacing the CIEDE2000 with the Euclidean color-difference formula for small-medium color differences in log-compressed OSA-UCS (Optical Society of America's committee on Uniform Color Scales) space [7], [8]. Our attempt has been inspired by the study [9], where the UCS diagram based on CIELUV color space is used to evaluate two color difference formulae ∆E00 and ∆EE for measuring the visual data.…”
Section: Introductionmentioning
confidence: 99%